Clinical evaluation of a medical high dynamic range display. Issue 7 (10th June 2016) - Marchessoux, Cedric; de Paepe, Lode; Vanovermeire, Olivier; Albani, Luigi
Abstract : Purpose: Recent new medical displays do have higher contrast and higher luminance but do not have a High Dynamic Range (HDR). HDR implies a minimum luminance value close to zero. A medical HDR display prototype based on two Liquid Crystal layers has been developed. The goal of this study is to evaluate the potential clinical benefit of such display in comparison with a low dynamic range (LDR) display. Methods: The study evaluated the clinical performance of the displays in a search and detection task. Eight radiologists read chest x‐ray images some of which contained simulated lung nodules. The study used a JAFROC (Jacknife Free Receiver Operating Characteristic) approach for analyzing FROC data. The calculated figure of merit (FoM) is the probability that a lesion is rated higher than all rated nonlesions on all images. Time per case and accuracy for locating the center of the nodules were also compared. The nodules were simulated using Samei's model. 214 CR and DR images [half were "healthy images" (chest nodule‐free) and half "diseased images"] were used resulting in a total number of nodules equal to 199 with 25 images with 1 nodule, 51 images with 2 nodules, and 24 images with 3 nodules. A dedicated software interface was designed for visualizing the images for each session. For the JAFROC1 statistical analysis, the study is done per nodule category: all nodules, difficult nodules, and very difficult nodules. Results: For all nodules, the averaged FoMHDR is slightly higher than FoMLDR with 0.09% of difference. For the difficult nodules, the averaged FoMHDR is slightly higher than FoMLDR with 1.38% of difference. The averaged FoMHDR is slightly higher than FoMLDR with 0.71% of difference. For the true positive fraction (TPF), both displays (the HDR and the LDR ones) have similar TPF for all nodules, but looking at difficult and very difficult nodules, there are more TP for the HDR display. The true positive fraction has been also computed in function of the local average luminance around the nodules. For the lowest luminance range, there is more than 30% in favor of the HDR display. For the highest luminance range, there is less than 6% in favor of the LDR display. Conclusions: This study shows the potential benefit of using a HDR display in radiology.